ICONIC ENGLISH BUSINESS NAME AS A BRANDING TOOL IN THE RURAL AREAS OF YOGYAKARTA SPECIAL REGION - Tur, Ajar Pradika Ananta (LITERA, 2019)
Abstract Today, people view foreign languages such as English as having more valuable attraction than the vernaculars to influence people. This condition is benefiting the businessmen to use English as a branding tool that they believe to be more effective and efficient to attract consumers ignoring the vernaculars. This study aims to describe the name of an English-language business as a branding tool in the area of the Yogyakarta Special Region.The method used in this research was descriptive qualitative with some quantitative features to support the analysis. The data were obtained from the rural areas of Yogyakarta Special Region through fieldwork using recorded interview with the owners of companies with a purposive sampling strategy. The data were analyzed by transcribing the interview, categorizing and analyzing the data, and drawing the conclusion. The results of this research show that the use of English as a branding tool in the rural areas of D.I. Yogyakarta signifies the names of institutions such as Barbershop, Laundry, Pet Shop, Photocopy Center, Cell-Phone Counter, Coffee Shop, and Homestay/Guest House. Those English names would be an icon to what they offer, give a guarantee of good quality, and offers high income. Even, they are orally becoming new vocabulary items for the people replacing the vernacular in naming the companies. Keywords: foreign language, branding, icon, business name, rural area NAMA IKONIK BISNIS BERBAHASA INGGRIS SEBAGAI ALAT BRANDING DI AREA PINGGIRAN DAERAH ISTIMEWA YOGYAKARTA Abstrak Dewasa ini, masyarakat memandang bahasa asing seperti bahasa Inggris mempunyai nilai lebih daripada bahasa lokal untuk menarik masyarakat. Kondisi ini menguntungkan bagi para pebisnis untuk memilih Bahasa Inggris sebagai media branding yang mereka percaya merupakan media yang efektif dan efisien untuk menarik perhatian pelanggan tanpa mengindahkan bahasa lokal mereka. Penelitian ini bertujuan mendeskripsikan nama bisnis berbahasa Inggris sebagai alat branding di area pinggiran Daerah Istimewa Yogyakarta. Metode yang digunakan dalam penelitian ini adalah penelitian deskriptif kualitatif yang dilengkapi beberapa komponen kuantitatif untuk mendukung analisis. Data diperoleh dari daerah-daerah rural di D. I. Yogyakarta melalui observasi lapangan, wawancara dengan pebisnis yang dipilih menggunakan teknik purposive sampling. Data wawancara yang terkumpul ditranskripsikan, dikelompokkan, dianalisis, dan disimpulkan. Hasil penelitian menunjukkan bahwa penggunaan Bahasa Inggris sebagai media branding di daerah rural di D. I. Yogyakarta ditampilkan dalam bentuk nama perusahaannya seperti Barbershop, Laundry, Pet Shop, Photocopy Center, Cell-Phone Counter, Coffee Shop, and Homestay/Guest House. Nama-nama tersebut menjadi ikon terhadap produk-produk sejenis, memberikan garansi kualitas, dan pendapatan tinggi. Bahkan, nama-nama tersebut menjadi kosakata baru yang menggantikan nama-nama produk sejenis dalam bahasa lokal. Kata kunci: bahasa asing, branding, ikon, nama perusahaan, daerah rural